Innovative functional juice enriched with native probiotics for enhanced nutrition and antimicrobial properties - Tenea, Gabriela N.; Perugachi, Erika (Frontiers in Nutrition, 2025)
IntroductionThe increasing demand for consuming highly nutritional value foods based on fruits or vegetables in combination with “beneficial” lactic acid bacteria (LAB) expands the research on developing novel functional non-diary delivery vectors.MethodsIn this study, the native Lactiplantibacillus plantarum UTNCys5-4 (Cys5-4) and commercial Lactiplantibacillus plantarum ATCC8014 (LP) strains have been targeted for probiotic properties in a novel designed tropical beverage containing yellow passionfruit (maracuyá) and coconut (MC). Furthermore, the quality of the newly fortified beverages, MCA (MC + Cys5-4) and MCB (MC + LP), was evaluated, along with their antimicrobial activity against two foodborne pathogens.ResultsThe results showed greater cell viability of Cys5-4 (8.84 ×107 CFU/ml), whereas a statistically significant (p < 0.05) decrease was registered for LP strain (1.90 × 105 CFU/mL) on the 15th day of storage with refrigeration. An enhanced ascorbic acid content (AAC) and total polyphenol content (TPC) in both fortified juices (MCA and MCB), with MCA showing moderate TPC increases and MCB showing slightly higher improvements. Both fortified juices exhibited increased antioxidant capacity (AOX) compared to the non-fortified control (MC), emphasizing their enhanced functional value. An intrinsic inhibitory activity against Salmonella enterica subsp. enterica ATCC51741 and Escherichia coli ATCC25922 was observed in the MC juice during the first 6 days of storage, after which the activity was lost. In contrast, the inhibitory activity in both MCA and MCB juices increased up to 15 days of storage, suggesting a synergistic interaction between the antimicrobial compounds produced by the bacteria and those naturally present in the fruit, effectively enhancing their role as in situ antimicrobial agents. These findings validate the use of Cys5-4 as a promising probiotic strain for developing functional beverages with improved shelf life, sensory properties, and health-promoting benefits.ConclusionThe synergistic antimicrobial and antioxidant effects underscore the potential of combining probiotics with tropical fruits like yellow passionfruit and coconut for innovative and nutritionally valuable non-dairy food products. These formulations present a promising solution for delivering native LAB strains, enabling the fruit and dairy industries to create healthier, market-driven products.